Emerging toxicity models from emerging scientists. Issue 3 (27th October 2014) - Allard, Patrick
Graphical Abstract: Abstract: Toxicology has seen a recent influx of new talents from other fields attracted by the application of their expertise to pressing questions of toxicological and environmental relevance. This transition has opened the door to innovative and exciting scientific opportunities but has also generated a new set of questions and challenges. In this viewpoint article, I will highlight some of the drivers and hurdles encountered by the recent new breeds of toxicologists.